Dynamin-Related Protein 1 as a therapeutic target in cardiac arrest - Sharp, Willard W. (J Mol Med (Berl), 2015)
Despite improvements in cardiopulmonary resuscitation (CPR) quality, defibrillation technologies, and implementation of therapeutic hypothermia, less than 10% of out-of-hospital cardiac arrest (OHCA) victims survive to hospital discharge. New resuscitation therapies have been slow to develop, in part, because the pathophysiologic mechanisms critical for resuscitation are not understood. During cardiac arrest, systemic cessation of blood flow results in whole body ischemia. CPR, and the restoration of spontaneous circulation (ROSC), both result in immediate reperfusion injury of the heart that is characterized by severe contractile dysfunction. Unlike diseases of localized ischemia/reperfusion (IR) injury (myocardial infarction and stroke), global IR injury of organs results in profound organ dysfunction with far shorter ischemic times. The two most commonly injured organs following cardiac arrest resuscitation, the heart and brain, are critically dependent on mitochondrial function. New insights into mitochondrial dynamics and the role of the mitochondrial fission protein Dynamin-related protein 1 (Drp1) in apoptosis have made targeting these mechanisms attractive for IR therapy. In animal models, inhibiting Drp1 following IR injury or cardiac arrest confers protection to both the heart and brain. In this review, the relationship of the major mitochondrial fission protein Drp1 to ischemic changes in the heart and its targeting as a new therapeutic target following cardiac arrest are discussed.